ChemInform Abstract: Constructing Coordination Nanocages: The Metalloligand Approach. Issue 38 (3rd September 2015) - Li, Li; Fanna, Daniel J.; Shepherd, Nicholas D.; Lindoy, Leonard F.; Li, Feng
Abstract Review: 31 refs.